Gluteal region spindle cell variant embryonal rhabdomyosarcoma in infant treated with buttockectomy - Nurjati Chairani Siregar; Ali Abdullah; Achmad Fauzi Kamal (Elsevier, 2019)
Introduction: Rhabdomyosarcoma (RMS) is a soft tissue tumor developed from immature mesenchymal cells and accounts for about one-half of soft tissue sarcomas in children. However, it is very rare in infants and so, little is known about. Spindle cell variant of embryonal RMS is a rare and a better differentiated variant of embryonal RMS, having a better prognosis compared to other types of rhabdomyosarcomas. So, it needs to be distinguished from classical forms of the neoplasm. Its morphological resemblance to spindle cell neoplasms like leiomyosarcomas and fibrosarcomas may pose diagnostic difficulties for the pathologist. Gluteal region is a rare site for RMS. We report an infant with embryonal spindle cell variant RMS in the gluteal region. Case report: A one-year-old infant appeared with a history of a two-month lump on the right buttock. Her mother started to notice asymmetry on her child's buttock when she was bathing him. She noticed a lump with the size of a ping-pong ball. The patient could still crawl as usual and walk with aid. Two months later, the lump grew to the size of a tennis ball. In spite of this condition, there was no complaint of fever, weight loss or signs of pain. On the MRI, the mass appeared hypo-intense at muscle on T1-weighted images and hyper-intense on T2-weighted images. Following the administration of dimeglumine-gadopentetate contrast, T1-weighted fat-saturated scans showed intense enhancement with interspersed non-enhancing areas. We decided to do a buttockectomy followed by an adjuvant chemotherapy. Results and discussion: Initially, the incision was performed from the posterior iliac crest curving distally following the gluteus maximus muscle until the 2 cm distal of greater trochanter. The incision was curved slightly posterior back to the medial aspect of the thigh to the gluteal fold to form a large posterior skin flap. Sciatic nerve had been identified and preserved. The entire gluteus maximus muscle with the mass has been removed. After 6 months of follow-up treatments, the patient is able to walk in normal gait and accordance with his mileage. Conclusion: The spindle cell embryonal rhabdomyosarcomas is a rare variant of embryonal subtype of RMS, occurring more commonly in children and adolescents. Its less aggressive sarcoma and better prognosis in children or adolescents, establish the correct diagnosis crucial using combination of clinical finding, histopathology and Immunohistochemistry. Keywords: Embryonal Rhabdomyosarcoma, Spindle Cell Variant, Gluteal Region, Infants, Buttockectomy